REFLECTIONS REGARDING LOST GRAVESTONE OF SERBIAN PRINCESS BRNČA, THE DAUGHTER OF KING UROŠ THE FIRST AND HELEN COMNEN COURTNEE OF ANJOU (Heritage, 2022)
Princess Brnča, daughter of king Uroš the First and his second wife Helen Comnen Courtne Anjou(from his previous marriage he had a son, Stefan), whose existence was unknown to historical sources, can be only noticed on portrait in frescos of lineage of dinasty of Stefan Nemanja in monasteries of Gračanica, Dečani and Patriarchate of Peć. Although she is nowhere presented as a nun, there is  presumption that she became a nun and that she was buried in the Monastery of Gradac, which is the foundation of her mother Helen Of Anjou. Hungarian sources testifiy that King Uroš The First had a son in law, whose name was unknown to history (the son of serbian great penitentiary), and Josif Tronožac claimed that the king had two daughters. There is a fact that Brnča was married to a certain mayor Đorđe, as well as the presumption that she was born around 1253.Newly discovered signature on the gravestone found in church of St. George, belonging to deserted and vanished, monastery Kastaljani, on the slopes of Kosmaj mountin, near Mladenovac, serves as a testemony  that this church was built by King Milutin in 1303, and that Brnča was buried there in 1306. This fact serves to reject completely all assumptions that are without any physical evidence that princess  Brnca was a nun and that she was buried in the monastery of Gradac. Knowing this, it can be concluded that the church of St. George  was built on the land that belonged to Princess Brnča and her husband, Mayor Đorđe, in the state of her brother, The king of Srem, Dragutin. The church must have stareted being built before war conflicts  between brothers, kings Milutin and Dragutin, around 1303 and 1304, and the other daughter of King Uroš The First, whose name remains unknown, is buried in the monastery of Gradac with her mother, Helen of Anjou.
Keywords: King Uroš the First, Queen Helen Comnen Courtne Anjou, Princess Brnča, castle Brnjaci, Monastery of Gradac, Monastery of Kastaljan